PENGARUH FAKTOR PERILAKU TERHADAP KEPUTUSAN INVESTASI - Aditya Wahyu; Yeye Susilowati (ITB AAS INDONESIA Surakarta, 2021)
This study aims to see the effect of anger, anxiety, overconfidence, herding effect, and self-monitoring. Investment decisions consist of investment experience, predictability of stock trends, investment amount, investment period, investment options, risk and return preferences, investment losses, and investment gains. The object of variable x is anger, anxiety, Overconfidence, Herding Effect, Self-Monitoring and variable y is investment decision. The sample data studied were 60 students of Stikubank University Semarang, the 2017 night class accounting study program, which were sampled and selected randomly. The data collection technique used in this study was a questionnaire method which was distributed directly to all respondents. The results of this study indicate that the variables of anger, anxiety, herding effect, and self-monitoring can have an influence on investment decisions in the S1 accounting study program for the evening class students of Stikubank University Semarang. Meanwhile, the overconfidence variable has no effect on investment decisions for students at Stikubank University Semarang in the 2017 night class accounting study program Keywords: Anger traits, anxiety traits, herding effect, self – monitoring, overconfidence.